Bibliometric study of neuroinflammation in autism spectrum disorder - Shen, Yingying; Zhong, Jiu-Gen; Lan, Wan-Ting; Li, Yin-Hua; Gong, Jia-Heng; Zhao, Ben-Xuan; Hou, Xiao-Hui (Frontiers in Psychiatry, 2023)
Abstract BACKGROUND: Neuroinflammation is closely associated with the occurrence and development of autism spectrum disorder (ASD). This study aims to describe the global development history and current status of neuroinflammation in ASD from 2004 to 2021 and reveal the research hotspots and frontiers to provide a reference for scholars in related fields to carry out further research. METHODS: Journal articles on ASD and neuroinflammation-related research were obtained from the Web of Science Core Collection (WOSCC) database from its inception to 2021. Literature was analyzed visually by VOSviewer, CiteSpace, and R language, including publication analysis, author, institution, national/regional cooperative network analysis, and keyword analysis. We screened the most accumulatively cited 10 experimental papers in the field and the most cited 10 experimental papers in the last two years (2020 and 2021) for combing. RESULTS: A total of 620 publications were included in this study, and the number of publications has increased in recent years. The United States (256,41.29%) was the country with the largest number of publications. King Saud University (40,6.45 %) was the most published institution; Laila Al-Ayadhi Yousef was the most published researcher; the Brain Behavior and Immunity was the main journal for the study of neuroinflammation in autism, having published 22 related articles. Keyword co-occurrence analysis showed that short chain fatty acid, mast cells, and glial cells have been the focus of recent attention. Burst keywords show that gut microbiota and immune system are the future research trends. CONCLUSION: This bibliometric study describes the basic framework for the development in the field of neuroinflammation and ASD through an exploration of key indicators (countries, institutions, journals, authors, and keywords). We found that the key role of neuroinflammation in the development of ASD is attracting more and more researchers’ attention. Future studies can investigate the changes in cytokines and glial cells and their related pathways in ASD neuroinflammation. Immunotherapy to inhibit neuroinflammation may be intensively studied as a direction for ASD treatment or intervention.